On the regularized trace of a second order differential operator - Gul, Erdal (ELSEVIER SCIENCE INC, 2008)
We calculate a regularized trace formula for a second order differential operator with bounded operator coefficient given in a finite interval. (c) 2007 Elsevier Inc. All rights reserved.
Keywords: hilbert space; adjoint operator; Kernel operator; spectrum and regularized trace; Mathematics